CSR Moderation Effects on the Influence of Capital Structure, Dividend Policy, Profitability on Firm Value (Studies on Food and Beverage Companies in Indonesia, Malaysia and Singapore in 2019-2021): Studies on Food and Beverage Companies in Indonesia, Malaysia and Singapore in 2019-2021 - Christine Benedicta Sutanto; Sugeng Hariadi (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
This study aims to determine the effect of capital structure, dividend policy and profitability on firm value with corporate social responsibility as a moderating variable. The sample for this research are food and beverage companies listed on the Indonesia Stock Exchange, Malaysia Stock Exchange and Singapore Stock Exchange in 2019-2021. Samples were taken using purposive sampling method and 108 samples were obtained. Data analysis used is descriptive statistics, R-square and path coefficient, with data processing using SmartPLS 4. The results show that capital structure, dividend policy and profitability have a significant effect on firm value. Meanwhile, social responsibility is not able to moderate the effect of capital structure, dividend policy and profitability on firm value.